Raising awareness of bronchiectasis in primary care: overview of diagnosis and management strategies in adults - James D. Chalmers (Nature Portfolio, 2017)
Abstract Bronchiectasis is a chronic lung disease characterised by recurrent infection, inflammation, persistent cough and sputum production. The disease is increasing in prevalence, requiring a greater awareness of the disease across primary and secondary care. Mild and moderate cases of bronchiectasis in adults can often be managed by primary care clinicians. Initial assessments and long-term treatment plans that include both pharmacological and non-pharmacological treatments, however, should be undertaken in collaboration with a secondary care team that includes physiotherapists and specialists in respiratory medicine. Bronchiectasis is often identified in patients with other lung diseases, such as chronic obstructive pulmonary disease, asthma, and in a lesser but not insignificant number of patients with other inflammatory diseases, such as rheumatoid arthritis and inflammatory bowel disease. Overall goals of therapy are to prevent exacerbations, improve symptoms, improve quality of life and preserve lung function. Prompt treatment of exacerbations with antibiotic therapy is important to limit the impact of exacerbations on quality of life and lung function decline. Patient education and cooperation with health-care providers to implement treatment plans are key to successful disease management. It is important for the primary care provider to work with secondary care providers to develop an individualised treatment plan to optimise care with the goal to delay disease progression. Here, we review the diagnosis and treatment of bronchiectasis with a focus on practical considerations that will be useful to primary care.